2008
DOI: 10.1007/s11269-008-9358-1
|View full text |Cite
|
Sign up to set email alerts
|

Indicators and Aspects of Hydrological Drought in Lebanon

Abstract: Change in climate conditions has become a global issue that has given a serious concern by many researchers. However, the availability of data in this regard is considered as a major element for optimum comparative analysis. The Mediterranean region is influenced by climate change, which is reflected mainly by its impact on water sources supply and flow regime. In Lebanon, these water sources are witnessing obvious quantitative decrease, thus affected the supply side, the socalled "hydrologic drought". Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…Given the torrential nature of rainfall in the Country reaching 30 mm h −1 (Shaban, 2008) and the absence of water diverting structures and sedimentation ponds in the vicinity of abandoned quarries, the risk of surface soil erosion and sedimentation in lowland areas and surface water streams is high on disturbed slopes, especially where plant cover was removed or intensively degraded. In the absence of adequate rehabilitation measures, the risk of runoff and erosion increases which multiplies the risk of sedimentation on arable lands and potential surface water contamination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the torrential nature of rainfall in the Country reaching 30 mm h −1 (Shaban, 2008) and the absence of water diverting structures and sedimentation ponds in the vicinity of abandoned quarries, the risk of surface soil erosion and sedimentation in lowland areas and surface water streams is high on disturbed slopes, especially where plant cover was removed or intensively degraded. In the absence of adequate rehabilitation measures, the risk of runoff and erosion increases which multiplies the risk of sedimentation on arable lands and potential surface water contamination.…”
Section: Resultsmentioning
confidence: 99%
“…It has rich biological diversity comprising of 2486 identified animal species (fauna) and 2600 plant species (flora), with 92 endemic species mostly located on mountainous areas (Abi Saleh et al ., 1996). Nearly 2000 springs were identified that feed into 60 major intermittent streams and permanent rivers (Shaban, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…rivers and groundwater) are two times more vulnerable than sources with less human interference, (eg. snow cover and precipitation) (Shaban 2009). A number of draught monitoring indices have been used over the years, like the Reconnaissance Drought Index (RDI) (Tsakiris et al 2007), the Draught Severity Index (DSIe) (Pandey et al 2008), the Streamflow Draught Index (SDI) (Nalbantis and Tsakiris 2009), etc.…”
Section: Introductionmentioning
confidence: 99%
“…There is little study on the African and Asian sides (e.g. Ellouze and Abiba 2008;Knippertz et al 2003a, b;Shaban 2009).…”
Section: Introductionmentioning
confidence: 99%